A functional bread produced by supplementing wheat flour with high β-glucan hull-less barley flour - Koksel, Hamit; Cetiner, Buket; Ozkan, Kubra; Tekin-Cakmak, Zeynep Hazal; Sagdic, Osman; Sestili, Francesco; Jilal, Abderrazek (WILEY, 2024)
Background and ObjectivesHigh beta-glucan hull-less barley (cv. Chifaa) was used in functional bread production. Its technological and nutritional properties were compared with the one produced from bread wheat flour.FindingsIncreasing levels of whole barley flour supplementation resulted in consistent increases in the Farinograph water absorption due to the high hydration capacity of beta-glucan in barley flour. Increasing whole barley flour supplementation levels had significant deteriorative effects on all of the bread quality characteristics probably due to dilution of gluten proteins. On the contrary, the mineral, beta-glucan, and phenolic contents and antioxidant capacities of breads supplemented with Chifaa were significantly higher than those of the bread produced from bread wheat.ConclusionThe glycemic index (GI) of the bread supplemented with 60% barley flour (66.4) was medium while the GI of the 45% barley flour-supplemented bread (70.1) was very close to the limit value of the medium GI. The lower GI of the barley flour-supplemented breads might be attributed to their higher beta-glucan contents. The results indicated that 3 g of beta-glucan can be provided from barley flour-supplemented bread (at 45% and 60%), which is the limit to bear health claim.Significance and NoveltyThe results of the present study indicated that high beta-glucan hull-less barley can be used to produce functional breads with better nutritional properties. The findings of this study may provide insights that can contribute to the studies on functional foods.
Keywords: functional foods; glycemic index; hull-less barley; nutritional properties; wheat; ANTIOXIDANT ACTIVITY; PHENOLIC-COMPOUNDS; STARCH; FRACTIONS; EXTRUSION; FOODS; BRAN; DIET; Chemistry; Food Science & Technology